The rights of illegal workers injured at work: a study of the judicial dilemma in the United States - Guthrie, Rob; Taseff, R. (Kluwer Law International BV, 2007)
The engagement of ‘non-citizens’, ‘aliens’, and ‘undocumented workers’ for work raises a number of delicate employment law and policy issues. This paper considers the attitude of the courts in the United States (US) to the question of the rights of workers who work contrary to immigration laws (illegal workers)1 and will focus on the recent case law in relation to workers’ compensation entitlements. In the US the case law on the rights of illegal workers to workers’ compensation is unclear and heavily dependent upon local State legislation and judicial attitudes. It has also been heavily influenced by the Supreme Court decision of Hoffman Plastic Compounds v National Labor Relations Board, which dealt with the rights of undocumented workers to make claims for wages consequent upon unfair termination of the employment contract. This paper explores the different judicial and legislative approaches to the rights of illegal workers to workers’ compensation, and proposes a possible humanitarian response to the difficult problem of the injured illegal worker.